2018
DOI: 10.7120/09627286.27.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Mortality resulting from undesirable behaviours in dogs aged under three years attending primary-care veterinary practices in England

Abstract: Undesirable behaviours (UBs) are common in dogs and can jeopardise animal and human health, leading to dog abandonment and euthanasia. Dogs exhibiting UBs may have compromised welfare from underlying emotional motivations for the behaviour (e.g. anxiety) or from how owners might seek resolution (e.g. aversive techniques). The objective of this study was to estimate proportional mortality due to UBs and risk factors for death due to UBs, including death from road traffic accidents, in dogs under three years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 49 publications
8
66
1
Order By: Relevance
“…Aggression is a complex topic and can be highly context-dependent in dogs [40] and therefore the causes of aggression and resultant treatment plans are likely to vary widely between individual dogs. The current study identified a higher prevalence for aggression in males compared with females (4.9% versus 3.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggression is a complex topic and can be highly context-dependent in dogs [40] and therefore the causes of aggression and resultant treatment plans are likely to vary widely between individual dogs. The current study identified a higher prevalence for aggression in males compared with females (4.9% versus 3.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The current study identified a higher prevalence for aggression in males compared with females (4.9% versus 3.5%). A male predisposition to aggression is supported by a substantial body of evidence for several breeds [40][41][42][43][44][45]. A deeper understanding of this predisposition, including whether different interventions may be required for male or female dogs to either prevent the development of aggressive behavior, or treat it once established requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although euthanasia entails an artificial foreshortening of lifespan, its time of occurrence often represents the approximate point at which the dog’s life is adjudged by the owner and the veterinarian to no longer be ‘worth’ living, either for ethical reasons pertaining to impairment of quality of the dog’s life and/or due to convenience in terms of management (of illness or behaviour) [ 29 , 30 ]. The balancing of the objectives of length and quality of life has particular poignancy for euthanasia due to behavioural rather than physical health problems (notably aggression, which accounted for 85, or 1.5% of, deaths in the current study), since these undesirable behaviours may be substantially influenced by environmental influences unique to the individual, including failures in management and training or unrealistic expectations by owners on how their dog should behave [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, causes of death with lower median ages at death may be viewed as life curtailing and possibly of greater welfare impact in the sense of years of potential life lost (e.g. road traffic accident, 3.21 years; aggression, 3.25 years; epilepsy, 5.67 years) [ 32 ]. These disorder-based longevity data offer insights that can assist with disorder prioritisation for reforms within breeds that can optimise the welfare gains from the effort and resources expended.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, whilst many still play an important role as working dogs [3][4][5][6], the most common reason for owning a dog is companionship [7]. Despite the fact that the role of pet dogs in Western cultures has been elevated to the status of a family member [8], there are several factors that can negatively affect the quality of the dog-human bond, with aggression being the most serious [9,10]. Aggressive behavior of dogs is expressed as aggressive biting, by snapping or attacking, and aggressive threatening, by growling, barking and baring their teeth [11].…”
Section: Introductionmentioning
confidence: 99%